THE INFLUENCE OF COACHING STYLE ON THE SOCIALIZATION OF YOUNG ATHLETES IN TEAM SPORTS (Scientific journal of the Fergana State University, 2026)
The socialisation of young team‑sport athletes is strongly influenced by coaching style. A 12‑week field experiment (n = 90; aged 11–15) compared authoritarian, democratic and laissez‑faire approaches. Democratic coaching produced significant gains in socialisation index (+ 43 %), team cohesion and coach–athlete relationship quality (p